Reconstitution of Mitotic Chromatids In Vitro. Issue 1 (24th May 2018) - Shintomi, Keishi; Hirano, Tatsuya
Abstract: The mitotic chromosome, which is composed of a pair of sister chromatids, is a large macromolecular assembly that ensures faithful transmission of genetic information into daughter cells. Despite its fundamental importance, how a nucleosome fiber is folded and assembled into a large‐scale chromatid structure remains poorly understood. To address this question, we have established a biochemically tractable system in which mitotic chromatids can be reconstituted in vitro by mixing a simple substrate (sperm nucleus) and a limited number of purified factors. The minimum set of required factors includes core histones, three histone chaperones, topoisomerase II, and condensin I. In this article, we describe a set of protocols for the preparation of key reagents and the setup of reconstitution reactions. We believe that this classical approach of biochemical reconstitution will be of great help to dissect the mechanisms of action of individual factors during mitotic chromatid assembly and to assess the contribution of nucleosome dynamics to this process from a fresh angle. © 2018 by John Wiley & Sons, Inc.